Civilising Globalism: Transnational Norm-Building Networks – A Research Programme - Ulrich Mückenberger (German Institute of Global and Area Studies (GIGA), 2008)
Decentralised, self-organised cross-border activities are increasingly shaping global policymaking. While state actors have lost ground, policy and economic networks have emerged as key actors, transforming international relations as well as national spheres. Academic discourse is following their activity, often focusing on 'advocacy networks' and on the role of transnational actors within the transformation of the world economy and world polity. In contrast to these research activities, the approach proposed here extends the scope of inquiry to include the role of transnational networks in norm-building and norm-implementation. The networks under scrutiny here do not confine themselves to the articulation of particular interests, the resolution of particular conflicts, or compliance with legal norms. It is presumed here that a variety of networks which are fundamentally concerned with the creation of norms have emerged. The predominance of the nation-state, one of the main characteristics of modern democratic thinking, has eroded to the point where the fundamental nexus of voice (democratic participation) and entitlement (legal and social rights and duties) has been weakened or even broken. We presume that this decentration has fundamentally changed the option of voice as one of the most important responses by citizens to crisis and change. This comes to the fore with the emergence and effectiveness of transnational norm-building networks. The article develops a research programme, the outcome of which will shed light on this new resource for the development of a democratised world polity. – – Dezentrale selbstorganisierte, grenzüberschreitende Aktivitäten gestalten zunehmend die globale Politik. Während Staaten an Bedeutung eingebüßt haben, sind politische und ökonomische Netzwerke zu Schlüsselakteuren geworden und transformieren sowohl internationale Beziehungen als auch nationale Politiken. Der akademische Diskurs konzentriert sich bei der Verfolgung von deren Aktivitäten oftmals auf 'Advokaten-Netzwerke' und die Rolle transnationaler Akteure bei der Umgestaltung von Weltökonomie und Weltpolitik. Die hier vorgestellte Forschungsinitiative erweitert demgegenüber den Untersuchungsrahmen auf die Rolle transnationaler Netzwerke bei der Normbildung und -durchsetzung. Die hier untersuchten Netzwerke erschöpfen sich nicht in der Artikulation von Partikularinteressen, der Lösung besonderer Konflikte oder dem Normgehorsam. Angenommen wird vielmehr, dass eine Vielzahl von Netzwerken entstanden ist, denen grundsätzlich an Normschaffung gelegen ist. Die Vorherrschaft des Nationalstaates, ein Charakteristikum modernen demokratischen Denkens, ist soweit erodiert, dass der grundlegende Nexus zwischen 'voice' (demokratischer Beteiligung) und 'Berechtigung/Verpflichtung' (hinsichtlich sozialer und rechtlicher Rechten und Pflichten) geschwächt oder gar gebrochen ist. Wir nehmen an, dass diese Art von Dezentrierung die voice-Option - als eine der wichtigsten Antworten von Bürgern auf Krise und Wandel - von Grund auf verändert hat. Dies kommt im Entstehen und Wirksamwerden transnationaler Normbildungsnetzwerke zum Vorschein. Der Artikel entwickelt ein Forschungsprogramm, das im Ergebnis Licht auf diese neue Ressource für die Entwicklung einer demokratisierten Weltordnung werfen wird.
Keywords: 300; networks; norms; world polity; globalisation; global civil society